2018
DOI: 10.3390/ma11122585
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Phosphatizing Coatings: The Effects of Preparation Conditions on Surface Properties

Abstract: Manganese phosphate coating could be used to protect the surface of steel products. However, it is essential to determine the effects which process parameters, as well as the types of additives used, have on the efficiency of coating deposition. Thus, we present here a process of phosphatization of low-alloy steel (for 15 min at 95 °C) in manganese/nickel baths followed by a passivation process with the use of a silicon and zircon compounds. The microstructure and morphology of the surface were analyzed by SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…On the basis of the tests of the cross-section of such coatings, it can be found that there are no two distinct border between the metal and the coating in the standard sample. The coating itself is produced from the substrate [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the tests of the cross-section of such coatings, it can be found that there are no two distinct border between the metal and the coating in the standard sample. The coating itself is produced from the substrate [8].…”
Section: Resultsmentioning
confidence: 99%
“…The methods include the conversion coating of metal with manganese phosphate [1][2][3][4][5][6][7]. During manganese phosphating, the steel product is submerged in a solution containing phosphoric (V) acid, nitric (V) acid and inorganic manganese and nickel compounds as well as organic phosphating accelerators containing NO 2 − nitro groups, e.g., nitro derivatives of benzene or nitro-compounds derived from guanidine [8].…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous washing liquids contain the remains of NaOH, KOH, phosphates, surfactants, detergents and emulsifying agent, -after digestion in hydrochloric acid. These washings contain chromium Cr 6+ , nickel Ni 2+ , large amounts of iron Fe 2+ from the etched metal, -after galvanization in a phosphating bath (bath composition: H 3 PO 4 , Mn 2+ compounds, Ni 2+ compounds, nitrates(V), sometimes chlorates and nitro compounds) [33][34].…”
Section: Characteristics Of Wastewater From Manganese Phosphate Coatingmentioning
confidence: 99%
“…wastewater from activation of the metal surface. Depending on the type of activating agent, it contains large amounts of inorganic acids or [33]. Another type of sewage is wastewater and washings from the passivation of metal surfaces.…”
Section: Characteristics Of Wastewater From Manganese Phosphate Coatingmentioning
confidence: 99%
See 1 more Smart Citation